Significant elimination of pore defect and interfacial reaction of sand casted Al–Li alloy castings via a novel inorganic binder coating - Yuancai Xu; Guangyu Li; Wenming Jiang; Junmin Zhan; Yang Yu; Zitian Fan (Journal of Materials Research and Technology, 2022)
Generally, sand casted Al–Li alloy castings have very serious problems in pore defect and interfacial reaction, remarkably weakening the Al–Li alloy castings quality. How to solve these problems is always a challenge. In this paper, a novel inorganic binder coating containing lithium silicate solution binder and silicon carbide powder on the surface of the sand mold was developed to eliminate pore defect and prevent interfacial reaction of the sand casted Al–Li alloy castings. The effective mechanism of the inorganic binder coating on the pore defect and interfacial reaction was discussed. The obtained results showed that the inorganic binder coating formed a thin shell on the surface of the sand mold after pouring, which can effectively prevent the metal-mold interface reaction of the sand casting Al–Li alloy and significantly reduce the porosity defects. Among them, the Al–Li alloy casting prepared using the inorganic binder coating consisting of the lithium silicate binder and silicon carbide powder basically had no pore defects, and the porosity was only 3.73%, which was 66.7% lower than that of the casting prepared by the sand mold without any treatment. Moreover, the interface reaction of the Al–Li alloy and sand mold was fully eliminated, which was attributed to the low overall atomic diffusion rate of the silicon carbide based on molecular dynamics simulation results.